Comparison of the Effect of High and Low Doses of Adrenocorticotropic Hormone (ACTH) in the Management of Infantile Spasms - Fayyazi, Afshin; Eslamian, Reihane; Khajeh, Ali; Dehghani, maryam (Iranian Journal of Child Neurology, 2020)
Introduction:Infantile spasmscan have irrecoverable adverse effects on a child’s brain. Adrenocorticotropic hormone (ACTH) is the most common first line medication for its treatment; however, the suitable dose and duration of treatment continue to be debated among specialists. The common high doses of this drug can produce more side effects; thus, lower doses are preferred. The aim of this study is to determine the effect and extent of complicationscaused by high and low doses of ACTH for children suffering from infantile spasms. Materials and methods:This study is a clinical trial in which 32 infants from 1.5 and 18 months of age suffering from infantile spasms were divided into high and low dose ACTH groups. Treatment lasted for two months. The therapeutic effects and their complications were then compared over the course of 18 months. Results:The results indicate thatthere were no significant differences between groups for short-term prognosis of controlling convulsions, final prognosis of patients for spasm relapse, EEG changes after treatment, post-treatment evolution and development of hypertension. However, there was a significant difference in the frequency distribution for intensity of restlessness and becoming Cushingoid, which were more frequent in the high dose group. Conclusion:These results indicate that high and low dose ACTH are equally effective in terms of controlling spasms, yet the low dose brings about fewer side effects.